(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Cow’s milk is a source of nutrients, including water, protein, carbohydrates, fat, vitamins, minerals and enzymes. However, it has been the target of criticism that raises doubts about its impact on human health, with cow’s milk consumption being associated with inflammatory processes. Objective: To map and analyze the information about cow’s milk as a pro-inflammatory factor disseminated by health professionals on the social networking platform Instagram®. Method: An exploratory study was carried out between 03/07/2023 and 03/11/2023 on the Instagram® social network. Brazilian health profiles were selected, such as doctors, nutritionists, physiotherapists, psychologists and nurses, regardless of gender, who had at least one image or video publication related to milk as an inflammatory factor. The publications were analyzed in terms of communicative practice, interaction with users, content and the quality of the information disseminated. Results: Publications in video format showed higher engagement when compared to those in image format. Among the opinions on cow’s milk, 9 profiles suggested an association with inflammation and a negative impact on health, while 11 profiles supported its consumption. 60% of the posts analyzed had no scientific articles to back up their views. Conclusion: The social network Instagram® has proved to be an important strategy for disseminating health-related content and citizen participation. However, it is necessary to consider the limits and challenges of its use, especially the spread of unscientific information.